Systematic Literature Review on The Use of Gamification Approaches in Mastering the Periodic Table of Elements (Chemistry) - Suzinursolahah binti Saleh; W Omar Ali Saifuddin Wan Ismail (Yayasan Adra Karima Hubbi, 2024)
Background: Gamification applications serve as tools for students to independently construct knowledge about lesson content, potentially surpassing achievements gained through conventional methods. The study of gamification is especially important for learning the Periodic Table of Elements, a fundamental topic in chemistry. Purpose: This article aims to explore the application of gamification in learning the Periodic Table of Elements between 2019 and 2023. Methods: A systematic literature review was conducted using online databases such as Scopus and Web of Science to gather relevant information on the subject. Keywords like